2009
DOI: 10.1097/mpa.0b013e318197a62e
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Growth Factors Enhance the Potency of Islets In Vitro

Abstract: These findings suggest that adult beta cells have the potential to proliferate while maintaining their endocrine function, which can be improved through careful regulation of proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is suggested that MSCs may exert their effects via a combination of numbers of bioactive and immunoregulatory factors. Importantly, these growth factors have been shown to promote islet survival and enhance beta cell function in several published studies [16–18]. A recent study demonstrated that co‐infusion of MSCs with BM enhanced stable mixed chimerism, which was essential for the induction of islet graft survival [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that MSCs may exert their effects via a combination of numbers of bioactive and immunoregulatory factors. Importantly, these growth factors have been shown to promote islet survival and enhance beta cell function in several published studies [16–18]. A recent study demonstrated that co‐infusion of MSCs with BM enhanced stable mixed chimerism, which was essential for the induction of islet graft survival [19].…”
Section: Discussionmentioning
confidence: 99%